Crowdfunding as a financing instrument for sport in difficult times - analysis of crowdfunding projects in Germany during the COVID-19 pandemic - Hodeck, A.; Tuchel, J.; Hente, L.; Brunner, M. (Journal of Physical Education and Sport, 2021)
Introduction: The Corona pandemic has an impact on all areas of society, including sport and its financing. The importance of crowdfunding in the field of financing has risen during the last ten years rapidly. There is a lack of experience regarding crowdfunding in the field of sports. This article deals with the possibility of using crowdfunding as a financing alternative for sports organizations during the time of Covid-19 in Germany in order to investigate if crowdfunding can be used by sports organizations in times of crisis or not. Material and methods: A mixed method approach was chosen to answer the research questions. 24 crowdfunding projects related to the topic of Corona in Germany in 2020 initiated by sports organizations had been identified in order to be analyzed quantitatively. In addition, three project initiators were interviewed qualitatively to identify opportunities and risks of this form of financing and to derive recommendations for future financing of sports organizations. Results & discussion: All financing projects have been successful regardless the type of the organization initiating the project, the type of sports of the project and the amount of money expected within the project. Qualitatively, apart from the pure successes in terms of crowdfunding revenues, there are some challenges for sports organizations to ensure the sustainable success of such projects. These include, above all, human and digital resources, which have hardly existed up to now.A positive aspect is the cohesion perceived by the initiators, not only among the supporters but also between different sports organizations. It remains to be seen whether this will also be so intense outside of a crisis such as the Covid-19 pandemic. Nevertheless, crowdfunding as a whole represents a real opportunity for the financing of sports organizations, not only in times of crisis.